Betamethasone and vision loss: An alarming side effect! - Anis, Muhammad Wajeeh; Mansoor, Mina; Younus, Mohammad Ijlal (Journal of the Pakistan Medical Association, 2023)
Madam, Betamethasone is a potent steroid medication with immunosuppressive and anti-inflammatory properties, and it is frequently prescribed in Pakistan for conditions such as eczema, psoriasis and contact dermatitis due to its availability and affordability. However, it has significant adverse effects such as skin atrophy, striae and other cutaneous symptoms, and glaucoma.[1] Glaucoma is a severe condition characterized by pathologic elevation in intraocular pressure, leading to optic nerve damage and irreversible blindness. As highlighted by Sahni et al. topical steroid use in the periorbital area for an extended peri, for treating eczema can lead to detrimental visual problems and glaucoma [2]. In this case, a woman taking high dose topical steroids since the age of 16 started to develop frequent falls and blurring of vision. She had markedly elevated intraocular pressures and extensive peripheral visual field loss, consistent with advanced glaucoma. In addition to the study above Charles et al. also published a case report about a 43-year-old male who used betamethasone ointment on his body for eight months straight. Although he had precisely denied using the ointment near his eyes, he developed painless vision loss in his left eye due to glaucoma.[3] Additionally, a 2017 study highlighted a significant rise of vision impairment in Pakistan, an increase of 55% since 1990, with glaucoma prevalent in 0.14 million individuals, and eye diseases to further increase by 2025.[4] Consequently, this medication, which is being discontinued around the world, is still frequently used in Pakistan. Through this manuscript, I would like to bring this serious issue to light so that people in Pakistan can also be educated and protected from this serious side effect. Healthcare practitioners should strictly be avoiding this medication and using less harmful alternatives.